Is insertion of a plastic stent better and safer than epinephrine injection in post sphincterotomy bleeding? - Schmitz, Daniel; Weller, Niels; Doll, Matthias; Werle, Stephan; Mees, Claus; Prinz, Peter; John, Barbara; Schmidt, Dorothea; Guenther, Andreas; Weiß, Christel; Rudi, Jochen (European journal of gastroenterology & hepatology, 2020)
Objectives Epinephrine injection is the therapy of first choice in post sphincterotomy bleeding (PSB), but may not be efficient in all cases and can cause postprocedural myocardial infarction. Plastic stent insertion (PSI) may be a better treatment. The aim of this retrospective study was to compare epinephrine injection with PSI with respect to efficacy and safety. Methods Clinical success, number of reinterventions and hospital stays after therapy, postprocedural myocardial infarction, bilirubin increase, and pancreatitis as well as factors influencing PSB were analyzed. Results Seventy-nine PSBs in 5798 endoscopic retrograde cholangiopancreaticographies (ERCPs) from August 2002 through October 2018 were treated by epinephrine injection, PSI or both (n = 34, 30, 15). Clinical success of PSB therapy showed no difference: 33/34 (97%), 30/30 (100%), 14/15 (93%). Reinterventions were more frequent (n = 30 versus n = 1; P <= 0.0001) and hospital stay was longer [median: 3 (2-10) versus 2 (1-3) days; P = 0.0357] in patients who received PSI (versus epinephrine injection). Postprocedural adverse events were very rare: bilirubin increase (1/2/0) and pancreatitis (0/2/1). Intraprocedural episodes of hypertension (>= 180 mmHg) were documented in 45-54%. Conclusions Epinephrine injection is better than PSI in PSB. PSI may be an adequate treatment in patients with otherwise indicated stent insertion. Intraprocedural episodes of hypertension may be a risk factor for PSB.
Gesehen am 27.05.2020